Deciphering the triad of endothelial glycocalyx, von Willebrand Factor, and P-selectin in inflammation-induced coagulation - Ferreira, Guinevere; Taylor, Alexandra; Mensah, Solomon A. (Frontiers in Cell and Developmental Biology, 2024)
This review examines the endothelial glycocalyx’s role in inflammation and explores its involvement in coagulation. The glycocalyx, composed of proteins and glycosaminoglycans, interacts with von Willebrand Factor and could play a crucial role in anchoring it to the endothelium. In inflammatory conditions, glycocalyx degradation may leave P-selectin as the only attachment point for von Willebrand Factor, potentially leading to uncontrolled release of ultralong von Willebrand Factor in the bulk flow in a shear stress-dependent manner. Identifying specific glycocalyx glycosaminoglycan interactions with von Willebrand Factor and P-selectin can offer insights into unexplored coagulation mechanisms.